Secondary metabolites from the leaves of Solanum melongena and their nitric oxide production inhibitory activity - Nhi, Nguyen Phuc Khanh; Phuong Ha, Tran; Tuan Anh, Le; Chi, Vu Thi Quynh; Cuong, Le Canh Viet (Vietnam Journal of Science and Technology, 2022)
Solanum melongena L. var. esculentum Ness. growing widely in Vietnam is a member of the plants family Solanaceae. Fruits and whole plant of S. melongena has been used by traditional medicine to treat various diseases, such as, toothache, turgescence, pruritus, and haemorrhoids. Previous studies indicated that this plant contain of alkaloids, anthocyanins, flavonoids, lignanamides, phenylpropanoid amides, sesquiterpenoids, steroids, steroidal saponins, and triterpenoids and exert diverse biological activities, such as anti-inflammatory, anti-cancer, anti-nociceptive, anti-oxidant, and anti-hypertensive activities. Using various chromatographic separations, four compounds were isolated from the leaves of Solanum melongena L growing in Thua Thien Hue province. Their chemical structures were elucidated to be quadranoside III (1), alangilignoside C (2), torvoside J (3), and N-trans-feruloyloctopamine (4) by 1D-, 2D-NMR spectra and compared with those reported in the literature. This study also reports the anti-inflammatory effect of isolated compounds via their inhibitory activity against the production of nitric oxide (NO) in RAW 264.7 macrophages cells stimulated by lipopolysaccharide. Compounds 1 and 4 showed NO inhibitory effects with IC50 values of 99.67 and 91.80 µM, respectively (posotive control L-NMMA, 32.26 µM), while compounds 2 and 3 were inactive. This is the first time that compound 1 has been reported from Solanum genus.